2018
DOI: 10.1093/cz/zoy091
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic shifts in perceptions of safety along structural complexity gradients in a territorial damselfish

Abstract: Age and body size can influence predation risk and hence habitat use. Many species undergo ontogenetic shifts in habitat use as individuals grow larger and have different age-specific predation pressures. On coral reefs, a number of fish species are more tolerant of threats in structurally complex habitats that contain more refuges than in less structurally complex habitats. However, we do not know how risk perception varies with age, and whether age interacts with habitat complexity. Adults and juveniles, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
3
2
Order By: Relevance
“…The positive estimate for hard substrate cover in our model implies that FID increased with hard substrate cover. These results differed from previous research which has suggested that the level of hard substrate cover was negatively associated with increased risk ( Chan et al 2019 ) but are in line with results presented in Cheh et al (2021) , which also detected a positive association between hard substrate and FID. Further previous research that differed from our results specifically tested the role of habitat structural complexity in risk assessment in a highly territorial damselfish species and found that fish in more complex habitats tolerated a closer approach ( Quadros et al 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The positive estimate for hard substrate cover in our model implies that FID increased with hard substrate cover. These results differed from previous research which has suggested that the level of hard substrate cover was negatively associated with increased risk ( Chan et al 2019 ) but are in line with results presented in Cheh et al (2021) , which also detected a positive association between hard substrate and FID. Further previous research that differed from our results specifically tested the role of habitat structural complexity in risk assessment in a highly territorial damselfish species and found that fish in more complex habitats tolerated a closer approach ( Quadros et al 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
“…One possible explanation for the difference is that the fish in areas with more hard substrate cover know that there are many hiding spots and it may be easier to hide rather than defend their territory. We did not find a significant result for SD in our model, which was similarly found in Chan et al (2019) but differed from results in Cheh et al (2021) where there was a significant main effect of SD in explaining FID variation. However, our experimental protocols differed slightly between this and previous studies because we waited for our subject to orient toward us and become motionless before we began our approach.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…It is important to note that the effects of habitat complexity may not be straightforward. For example, habitat complexity has been shown to decrease anxious behaviour in zebrafish ( Danio rerio ; DePasquale et al, 2016 ), fearful behaviour in fathead minnows (Crane, Ferrari, et al, 2020 ), and flight initiation distances in reef fishes (Chan et al, 2019 ; Nunes et al, 2015 ). In another study on the turquoise killifish ( Nothobranchius furzeri ), fish reared in complex environments were demonstrated to be less risk‐averse in novel habitats, but more risk‐averse in open habitats (Thoré et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This held both in absolute (cm) distances, and in the relative value of body lengths (which is presumably relevant to fish). The above differences in fish behavior may result from different costs of hiding or different perceived risks for small versus large fish [3,[34][35][36]. Small fish have higher metabolic cost of hiding [37] and are considered as less risk aversive [38,39].…”
Section: Discussionmentioning
confidence: 99%